2013
DOI: 10.1111/jvim.12061
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Fluorescent Antibody Test and Surface Antigen ELISAs for Antemortem Diagnosis of Equine Protozoal Myeloencephalitis

Abstract: Background: Recent research suggests that serum : CSF titer ratios could provide the most accurate antemortem diagnosis of equine protozoal myeloencephalitis (EPM) caused by Sarcocystis neurona.Objectives: The purpose of this study was to assess the utility of two commercially available tests, the indirect fluorescent antibody test (IFAT) and the surface antigen 2, 4/3 ELISA (SAG2, 4/3 ELISA), using archived paired serum and CSF samples.Animals: Samples were obtained from 4 types of clinical patients. Confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 10 publications
1
33
1
1
Order By: Relevance
“…This study also showed that minor blood contamination of the CSF sample (ie, up to 10,000 red cells per μL) will not confound the assay results. Subsequently, 2 additional studies examining a more extensive collection of horses with neurologic disease showed that a simple serum:CSF antibody titer ratio was sufficient in many cases for an accurate diagnosis of EPM caused by S. neurona 71, 72. Although use of a serum:CSF titer ratio should be equally effective for diagnosis of EPM caused by N. hughesi , an optimal serum:CSF titer ratio cut‐off needs to be established.…”
Section: Immunodiagnostic Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…This study also showed that minor blood contamination of the CSF sample (ie, up to 10,000 red cells per μL) will not confound the assay results. Subsequently, 2 additional studies examining a more extensive collection of horses with neurologic disease showed that a simple serum:CSF antibody titer ratio was sufficient in many cases for an accurate diagnosis of EPM caused by S. neurona 71, 72. Although use of a serum:CSF titer ratio should be equally effective for diagnosis of EPM caused by N. hughesi , an optimal serum:CSF titer ratio cut‐off needs to be established.…”
Section: Immunodiagnostic Testingmentioning
confidence: 99%
“…Descriptions of testing options and reported test performance are shown in Table 1 71, 72, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93. All tests can be performed on serum or CSF, and none is considered a gold standard.…”
Section: Immunodiagnostic Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The sarcocystis neurona causes a dreadful disease, equine protozoal myeloencephalitis (EPM) in equines. The IFAT was successfully validated for CSF testing for confirmation of EPM in equines (Duarte et al, 2006;Johnson et al, 2013).…”
Section: Fluorescent Antibody Test (Fat)mentioning
confidence: 99%